Rapid Assessment of Floating Macroplastic Transport in the Rhine - Vriend, Paul; van Calcar, Caroline; Kooi, Merel; Landman, Harm; Pikaar, Remco; van Emmerik, Tim (Frontiers in Marine Science, 2020)
Most marine litter pollution is assumed to originate from land-based sources, entering the marine environment through rivers. To better understand and quantify the risk that plastic pollution poses on aquatic ecosystems, and to develop effective prevention and mitigation methods, a better understanding of riverine plastic transport is needed. To achieve this, quantification of riverine plastic transport is crucial. Here, we demonstrate how established methods can be combined to provide a rapid and cost-effective characterization and quantification of floating macroplastic transport in the River Rhine We combine visual observations with passive sampling to arrive at a first-order estimate of macroplastic transport, both in number (10 - 75 items per hour) and mass per unit of time (1.3 – 9.7 kg per day). Additionally, our assessment gives insight in the most abundant macroplastic polymer types the downstream reach of the River Rhine. Furthermore, we explore the spatial and temporal variation of plastic transport within the river, and discuss the benefits and drawbacks of current sampling methods. Finally, we present an outlook for future monitoring of major rivers, including several suggestions on how to expand the rapid assessment presented in this paper.